Managing Wheat Blast: A Call for Coordinated Genetic, Chemical, and Quarantine Interventions (Journal of Agriculture and Veterinary Science, 2025)
Wheat blast is a highly destructive disease that has emerged as a significant challenge to wheat production in warm and humid regions, caused by the fungal microorganism Magnaporthe oryzae pathotype Triticum (MoT). The disease was first reported in Brazil in 1985, spread across South America and has been identified in Asia (Bangladesh and India) and Africa recently (South America, including Bolivia, Paraguay, and Argentina) raising concerns worldwide. This review summarizes the epidemiological development, transcontinental distribution, and phytosanitary implications of wheat blast, highlighting the urgent need for coordinated international surveillance, breeding for resistance, and strict seed health protocols to inhibit global incursions. Since its initial outbreak in Brazil, the pathogen has demonstrated a capacity for rapid transboundary spread and severe yield losses. Its recent emergence in South Asia has intensified concerns, prompting surveillance efforts in Pakistan. Encouragingly, recent findings indicate that major wheat-producing regions in the country remain free of the disease. Nonetheless, the potential for regional spread remains a significant concern. Despite the grave implications for agricultural productivity, food security, and rural livelihoods, wheat blast has historically received limited attention at the global level. If left unmanaged, it could lead to widespread socio-economic disruption, including food insecurity and rural displacement. This article outlines a proposed framework for managing the threat through an integrated disease management (IDM) approach. Key components include the development of genetically resistant cultivars, prudent fungicide application, strict phytosanitary measures, and enhanced international collaboration to curb transboundary movement. A holistic, science-led strategy—underpinned by genomics-assisted breeding, robust surveillance, and coordinated global policy responses—is essential to safeguard wheat-based food systems in both endemic and at-risk regions.